Shape of the Sagittal Curvatures of the Spine in Young Female Volleyball Players - Ewa Puszczalowska-Lizis; Wioletta Mikulakova; Patrycja Fitas; Sabina Lizis (Applied Sciences)
Background: The issue of the relation betweeen training loads on the shape of the spine of young players is of significant importance, as with the advancement of training seniority, unfavorable changes may be perpetuated resulting in possible consequences in the next stages of ontogenesis. The aim of this study was to assess the formation of the sagittal curvatures of the spine in girls practicing volleyball versus their nonpractising peers. Methods: We examined 60 girls aged 10–13 years, including 30 volleyball players and 30 untrained peers. The Baseline Bubble inclinometer was applied as a research. The data were analyzed based on Mann–Whitney U test and Pearson Chi-square test. Results. There were statistically significant intergroup differences in lumbar lordosis curvature values (Z = −2.67; p = 0.007). The prevalence of correctness values of the thoracic kyphosis curvature, was group-dependent (χ2(1) = 4.34; p = 0.037). Group also determined the prevalence of lumbar lordosis normalities (χ2(1) = 5.41; p = 0.020). Conclusions. Volleyball has a beneficial effect on the formation of the thoracic kyphosis, while the lumbar lordosis is shallowed under the influence of training. This indicates the need for a holistic approach to player training and the need to supplement the technique and tactics training with exercises to strengthen the muscles that stabilize the lumbar spine, improve spinal mobility, learn how to control the anterior tilt of the pelvis and train the fascia.